2020
DOI: 10.1182/bloodadvances.2019001307
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of driver mutations and their clinical impacts in pediatric B-cell precursor acute lymphoblastic leukemia

Abstract: Recent genetic studies using high-throughput sequencing have disclosed genetic alterations in B-cell precursor acute lymphoblastic leukemia (B-ALL). However, their effects on clinical outcomes have not been fully investigated. To address this, we comprehensively examined genetic alterations and their prognostic impact in a large series of pediatric B-ALL cases. We performed targeted capture sequencing in a total of 1003 pediatric patients with B-ALL from 2 Japanese cohorts. Transcriptome sequencing (n = 116) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…MEF2D (myocyte enhancer factor 2D) rearrangements occur in ~4% of childhood and 10% adult B-ALL cases. This subtype shows a distinct immunophenotype with low/absent expression of CD10, and positivity for CD38 and cytoplasmic µ chain, and distinct expression profiles [7,[85][86][87][88]. MEF2D is the 5 partner in all described fusions, whereas B-cell CLL/lymphoma (BCL) 9 and heterogeneous nuclear ribonucleoprotein U-like 1 (HNRNPUL1) are the two most recurrent 3 partners.…”
Section: Dux4 Mef2d Znf384 and Nutm1 Gene Fusionsmentioning
confidence: 99%
See 1 more Smart Citation
“…MEF2D (myocyte enhancer factor 2D) rearrangements occur in ~4% of childhood and 10% adult B-ALL cases. This subtype shows a distinct immunophenotype with low/absent expression of CD10, and positivity for CD38 and cytoplasmic µ chain, and distinct expression profiles [7,[85][86][87][88]. MEF2D is the 5 partner in all described fusions, whereas B-cell CLL/lymphoma (BCL) 9 and heterogeneous nuclear ribonucleoprotein U-like 1 (HNRNPUL1) are the two most recurrent 3 partners.…”
Section: Dux4 Mef2d Znf384 and Nutm1 Gene Fusionsmentioning
confidence: 99%
“…NUTM1 (nuclear protein in testis midline carcinoma family 1) rearrangements (<2% of childhood B-ALL and mostly infant without KMT2A-rearrangements) [7,13,88,[98][99][100] are characterized by fusion of NUTM1 to different partners, including transcription factors and epigenetic regulators (e.g., ACIN1, AFF1, ATAD5, BRD9, CHD4, CUX1, IKZF1, RUNX1, SLC12A6, and ZNF618), that drive aberrant NUTM1 expression [7,13]. In all fusions, the NUT domain is retained, and this is hypothesized to lead to global changes in chromatin acetylation [101] and to sensitivity to histone deacetylase inhibitors or bromodomain inhibitors in case of fusions with BRD9.…”
Section: Dux4 Mef2d Znf384 and Nutm1 Gene Fusionsmentioning
confidence: 99%
“…The different RAS signaling alterations have been shown to be mutually exclusive, suggesting that, in contrast to the convergent evolution for RAS mutations observed in infants with MLL-rearranged B-ALL [ 52 ], a single alteration in the pathway is sufficient to maintain constitutive RAS-pathway activation. Focal deletions or point mutations in NF1 gene are the most recurrent genetic alterations of near-haploid B-ALL (≥44% of patients) [ 23 , 30 , 53 ]. NF1 encodes a RAS–GTPase-activating protein that negatively regulates Ras signaling.…”
Section: Molecular Characterization Of Hypodiploid B-all With <40 Chromosomesmentioning
confidence: 99%
“…A recent study by the Japan Association Childhood Leukemia Study Group (JACLS) reported a high frequency of mutations in CIC in both low-hypodiploid and near-haploid B-ALL, present in 5 of 9 patients [ 53 ]. CIC is a member of the high mobility group (HMG)-box superfamily of transcriptional repressors and is recurrently mutated in oligodendrogliomas and in round cell sarcomas.…”
Section: Molecular Characterization Of Hypodiploid B-all With <40 Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation